Model for integrates community tourism in Ecuador, case study Pastaza - Reyes Vargas, María Victoria; Ortega Ocaña, Ángel Fernando; Machado Chaviano, Esther Lidia (REVESCO. Revista de Estudios Cooperativos, 2016)
The tourism industry globally has grown steadily in recent decades, showing a progressive interest oriented toward rural areas due to characteristics of tranquility, nature, biodiversity, traditions and culture. Therefore, such aspects should be preserved and can be leveraged through adequate strategic orientation. Within the framework of global tourism trends community tourism is among the options that arise in the tourism market, and is one that is more likely to grow in the future. In the case of Ecuador, community tourism has become more dynamic over the years since many of the natural reserves in the country are in the hands of indigenous communities. Sustainable tourism in this sense is concerned with the maintenance of ethnic, cultural and biological diversity of the country, and current projects and regulatory laws support its development. Therefore, the aim of this paper is to present a strategy for the integrated management of community tourism following the principles of cooperation and collaboration between stakeholders, this study focuses on the Amazon region of Ecuador, specifically the province of Pastaza, in respect to how community tourism contributes to local development